The Influence of the Enzyme Preparation Wobenzym on the Formation and Destruction of Biofilms Consisting of Non-Pathogenic, Opportunistic Bacteria and Fungi of the Genus Candida - A. V. Ustyuzhanin; G. N. Chistyakova; I. I. Remizova (Антибиотики и Химиотерапия, 2025)
Background. Numerous studies confirm the key role of bacterial and fungal etiological agents capable of film formation in the development of acute and chronic infectious processes, as well as the need to search for new methods of eradication of pathogens and destruction of biofilm.   The aim of the study was to examine the effect of the enzyme preparation Wobenzym on the process of formation and destruction of complex biofilms consisting of representatives of the normal microbiocenosis of the reproductive tract of women, opportunistic bacteria and fungi of the Candida genus.   Material and methods. 33 strains of bacteria and 16 strains of fungi with increased film-forming ability were studied using the bacteriological method.   Results. The average value of optical density (OD), reflecting the intensity of film formation, is 0.478 ± 0.240 (m = ±0.042) when cultivating strains without Wobenzym. The average OD value during cultivation with Wobenzym is 0.190 ± 0.162 (m = ±0.028), (P = 0.001). OD is significantly lower in wells with the enzyme preparation Wobenzym when cultivating both bacterial and fungal isolates and their associations. As the duration of cultivation increases, the intensity of film formation also increases. It has been established that the enzyme preparation Wobenzym leads to the destruction of a biofilm of bacterial and fungal strains formed within 24 and 48 hours, as well as their associations consisting of one, two, or three microorganisms.   Conclusions. The enzyme preparation Wobenzym reduces the film-forming ability of both bacterial cells and Candida fungi, reducing the likelihood of biofilm formation, which lowers the risk of relapse and confirms its potentiating effect in the treatment of infectious and inflammatory processes of both bacterial and fungal etiology. Wobenzym destroys complex biofilms consisting of both gram-positive, gram-negative, non-pathogenic, opportunistic, including ESBL-producing, bacteria and fungi of the genus Candida. The enzyme preparation Wobenzym does not inhibit the viability of representatives of the normal microbiocenosis of the female reproductive tract, such as Lactobacillus spp., which provide colonization resistance of the non-sterile locus of the human body.